Voltage balancing of a 320-V, 12-F electric double-layer capacitor bank combined with a 10-kW bidirectional isolated DC-DC converter - Tan N.M.L.; Inoue S.; Kobayashi A.; Akagi H. (2023)
double-layer capacitors (EDLCs) have attributes that feature high power density, quick charge/discharge time, long life cycle, and environmental friendliness. These attributes accord for increased appeal in employing the EDLCs as energy-storage devices in renewable energy systems, industrial applications, and hybrid electric vehicles as compared to other mature static energy-storage devices. This paper describes the construction of a 320-V, 12-F EDLC energy-storage bank connected to a bidirectional isolated dc--dc converter. Two types of EDLC bank configurations are considered with emphasis on their voltage-balancing circuits. Subsequently, this paper proposes a voltage-balancing circuit based on a center-tapped transformer, and includes its experimental verifications. It also discusses the charge--discharge and self-starting operation of the EDLC energy-storage system. During the charge--discharge operation, a low ripple current flowing in the EDLC bank is observed, leading to a theoretical analysis. The EDLC bank is also successfully charged to its rated voltage without any external dc charging circuit. 2008 IEEE.